2022
DOI: 10.7150/ijms.71127
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Wnt10a causes female infertility via the β-catenin/Cyp19a1 pathway in mice

Abstract: Wnt signaling is relevant for a wide range of biological processes, including reproductive function. The function of Wnt10a in female fertility, however, remains obscure. In the present study, we explored the structure and function of the female reproductive organs in Wnt10a knockout (KO) mice. The expression of β-catenin signaling was significantly lower in the ovaries of the Wnt10a KO mice compared with wild-type (WT) mice. In addition, the estrous cycles were disrupted, ovarian follicles were diminished, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Wnt10a -/- mice were grossly smaller in size when compared with WT mice of the same age ( Figure 1 A). The mean body weights and brain weights were significantly lower in Wnt10a -/- mice ( Figure 1 B,C), corresponding to previous reports [ 17 , 18 , 19 ]. Compared with WT mice, the hippocampal volume in Wnt10a -/- mice was significantly lower ( Figure 1 D,E).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Wnt10a -/- mice were grossly smaller in size when compared with WT mice of the same age ( Figure 1 A). The mean body weights and brain weights were significantly lower in Wnt10a -/- mice ( Figure 1 B,C), corresponding to previous reports [ 17 , 18 , 19 ]. Compared with WT mice, the hippocampal volume in Wnt10a -/- mice was significantly lower ( Figure 1 D,E).…”
Section: Resultssupporting
confidence: 90%
“…A typical disease caused by Wnt10a deficiency is odonto-onycho-dermal dysplasia, which has symptoms typically affecting skin, hair, and teeth [ 15 ]. Recent studies have indicated that Wnt10a plays an essential role in tumor growth, wound healing, osteogenesis, adipogenesis, and female fertility using Wnt10a -/- mice [ 16 , 17 , 18 , 19 ]. No reports, however, have examined the effects of Wnt10a on hippocampal structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the placenta is the main site of estrogen production and the most active site for CYP19A1 expression [ 57 ]. Decreased estrogen levels are associated with downregulated CYP19A1 expression in mouse granulosa cells [ 58 ]. Our results showed that a high dose of P4 promoted E2 synthesis, possibly due to the upregulation of CYP19A1 gene expression.…”
Section: Discussionmentioning
confidence: 99%